(untitled) (Law and Safety, 2020)
The subject matter of the research is theoretical and applied problems of criminal and legal qualification of domestic violence. Its purpose is to form propositions for solving these problems. The latter include the difficulties of unambiguous interpretation and legal assessment of the features of a socially dangerous act provided by the Art. 126-1 of the Criminal Code of Ukraine, and the features of “systematic”, establishing socially dangerous consequences and causal relation and distinguishing domestic violence from related corpus delicti of criminal offenses. The author has revealed the “interdiction” of socially dangerous results (as features of an action) and consequences, which leads to incompleteness and incorrect qualification. The solution of this problem is directly related to: a) the separation of psychological violence from those forms of psychological influence on a person that cannot be considered violence; b) separation of domestic violence as an administrative tort from a criminal offense. The author has suggested a two-dimensional model of the consequences of psychological violence, where the first (closer) level consists of those consequences defined in the Law of Ukraine “On Preventing and Counteracting Domestic Violence”, and the second (remote) level – in the Art. 126-1 of the Criminal Code of Ukraine. When there are sufficient grounds to believe that domestic violence is systematic, the use of prior administrative response procedures should be avoided after the first report or personal detection by the police officer. Special attention has been paid to the criteria for distinguishing between the legal components of domestic violence and criminal offenses against life and health, sexual freedom and sexual integrity, as well as those provided by the Articles 164 and 165 of the Criminal Code of Ukraine.